Biochemical and histopathological changes induced by sodium monofluoroacetate (1080) in mallard ducks - Ataria, J.M.; Wickstrom, M.; Arthur, D.; Eason, C.T. (New Zealand Plant Protection, 2000)
Public concern over inadvertent kills of native birds following largescale aerial poisoning operations for possum has highlighted deficiencies in information concerning the effects of 1080 on nontarget species In this study biochemical and histopathological changes were measured in adult male mallard ducks (Anas platyrynchos) dosed orally with 1080 The toxin was quickly absorbed into the blood and distributed to the cardiac tissue The time taken to reach maximum 1080 concentrations in these tissues corresponded closely with the onset of clinical signs of toxicosis Tissue and serum citrate accumulation is a direct result of 1080induced inhibition of the Krebs Cycle enzyme aconitate hydratase Histopathological lesions indicated that skeletal muscle was a target organ for 1080induced damage in birds Dosedependent increases in serum creatinine kinase (CK) and aspartate aminotransferase (AST) were consistent with extensive muscle necrosis Skeletal muscle may be a unique avianspecific target organ for 1080